2022
DOI: 10.7150/jca.73112
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MSMO1 promotes the development and progression of pancreatic cancer

Abstract: Background: Methylsterol monooxygenase 1 (MSMO1), as a completely unique tumor biomarker, plays a vital role in the malignant progression of various cancer. Until now, the potential function and pathway of MSMO1 in the development of pancreatic cancer (PC) has not been explored yet, to our knowledge. Methods: We systematically explored the detail function of MSMO1 in Epithelial-mesenchymal transition (EMT) and cell proliferation of PC in vitro and in vivo. Results: MSMO1 expression was much lower in PC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…[33] Furthermore, MSMO1 is involved in the biosynthesis and metabolism of sterols and cholesterol. [34] Previous studies reported that MSMO1 expression is up-regulated in cervical cancer [35,36] and down-regulated in hepatocellular carcinoma, [37] cholesterol synthesis in chondrocytes, [38] pancreatic cancer, [39] and iron overload, [40] which is consistent with our results. NCOA4 encodes a selective receptor that mediates ferritinophagy and the cytosolic iron storage complex [41,42] and plays a selective regulatory role in the case of iron deficiency or iron overload.…”
Section: Discussionsupporting
confidence: 92%
“…[33] Furthermore, MSMO1 is involved in the biosynthesis and metabolism of sterols and cholesterol. [34] Previous studies reported that MSMO1 expression is up-regulated in cervical cancer [35,36] and down-regulated in hepatocellular carcinoma, [37] cholesterol synthesis in chondrocytes, [38] pancreatic cancer, [39] and iron overload, [40] which is consistent with our results. NCOA4 encodes a selective receptor that mediates ferritinophagy and the cytosolic iron storage complex [41,42] and plays a selective regulatory role in the case of iron deficiency or iron overload.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrate that NLK can promote the occurrence and development of EMT in pancreatic cancer cells. However, due to different types of cancer and their associated cellular environments, the role of NLK may vary or even be opposite in different types of cancer [33] . Reports suggested that NLK overexpression can inhibit the occurrence of EMT and subsequently inhibit the proliferation and migration of non-small cell lung cancer (NSCLC) by affecting E-cadherin protein expression [34; 35] .…”
Section: Discussionmentioning
confidence: 99%
“…In our microarray analysis, we determined that downregulation is associated with different biological processes, including protein complexes involved in cell adhesion ( FZD7 ), vasculature development( PTGS2, C3, IL6 ), development of angiogenesis ( SERPINF, C3, ADAMTS1, HMOX1, CXCL8, PTGS2 ), cell migration ( PTGS2, CXCL12, CYGB, BMP2, LRRC15, CXCL8, ENPP2, HAS2, NR4A2), cell differentiation ( BMP2, LIF ), tube development (PTGS2, NR4A1, HSD11B1, ANG, LIF BMP2, ID1, ADAMTS1, HMOX1 ), and cell–matrix adhesion ( SNED1 ). Steroid and lipid metabolism, dysregulated cell proliferation, migratory activity, regulatory molecules in cell adhesion, and extracellular matrix play essential roles in the pathogenesis of pterygium (Cao et al., 2022; Kim et al., 2013; Liu et al., 2013).…”
Section: Discussionmentioning
confidence: 99%